2016
DOI: 10.1200/jco.2016.67.9647
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Update of a Multi-Institutional Predictive Nomogram for Salvage Radiotherapy After Radical Prostatectomy

Abstract: Early SRT at low PSA levels after RP is associated with improved FFBF and DM rates. Contemporary nomograms can estimate individual patient outcomes after SRT in the modern era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
277
7
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 321 publications
(301 citation statements)
references
References 21 publications
9
277
7
8
Order By: Relevance
“…This is lower than expected from the literature for biochemical response at this median PSA level (3). There are several possible reasons for this.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…This is lower than expected from the literature for biochemical response at this median PSA level (3). There are several possible reasons for this.…”
Section: Discussioncontrasting
confidence: 62%
“…It remains the last chance for cure in these men, with around 56% of men achieving complete biochemical response at 5 y after RT (2,3,11). Studies have shown that low serum PSA values after RP are correlated to significantly better treatment outcomes, supporting early SRT at a serum PSA of less than 0.2 ng/mL or less than 0.5 ng/mL (3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large studies have not yet demonstrated a clear benefit for adjuvant over early salvage treatment with radiation [4][5][6] . However, clinical evidence consistently suggests that early treatment with lower PSAs (≤0.2ng/ml) at the time of salvage radiotherapy is associated with improved treatment outcomes.…”
Section: ***mentioning
confidence: 99%
“…The interquartile range (IQR) for baseline PSA at the time of randomization on the GETUG trial was 0.2–0.5 ng/mL. A recent multi-institutional cohort found the PSA at the time of salvage radiotherapy to be significantly higher (IQR 0.3–1.1) (7). The men in the GETUG study, therefore, were referred for radiation therapy relatively early.…”
mentioning
confidence: 99%